Religious Learning Environments of Austrian Muslim Youth: An Empirical Analysis of Religious Educational Processes - Tuna, Mehmet Hilmi (Religions, 2023)
In recent decades, Islamic education and the religiosity of young Muslims have received considerable attention in academic research in German-speaking countries. However, an analysis of the different learning environments of religious education and their respective significance has yet to be carried out so far. Using Austria as an example, this paper explores these different processes of religious education among Muslim adolescents. Based on qualitative guided interviews, the experiences and learning processes in the family, in the mosque, in the school, and online are depicted from the learners’ perspective. In this way, this paper assigns Muslim adolescents a constitutive role in the analysis. In this context, we discuss how the understanding of education, pedagogical approaches, and person-centredness differs in the learning environments of Muslim religious education.